PENGARUH PELATIHAN CALL THE NUMBER DRILL DAN THREE CHAIR DRILL TERHADAP KETERAMPILAN DRIBBLING BOLA BASKET - I Kadek Suardika; Gede Hendri Ari Susila; Ketut Agus Artha (Jurnal Muara Olahraga, 2019)
The study aimed to determine (1) the effect of Made Or Run Drill training on shooting skills, (2) the effect of ten free throwing a row drill training on shooting skills, (3) differences in shooting skills between treatment groups made or run drill and ten free throws in a row drill. The sample of the study was 30 students of the SMAK TI Bali Global Singaraja basketball extracurricular students. This study uses a quasi-experimental method with the design of the modified pre-test-post-test group design. Data collection tests use the free throw shooting skill test. Data analysis uses t-test (t-test) statistical calculations at a significance level of 5%. The results of data analysis (1) training made or run drill have an effect on Basketball shooting skills, with the results of thit = 5.850> ttab = 2.145, (2) ten free throws in row drill training affects Basketball shooting skills, with results thit = 4,610> ttab = 2,145, (3) there is no difference in effect between training made or run drill and ten free throws in a row drill on shooting skills, with the results of thit = 0,000 <ttab = 2,048. Training of made or run drill and ten free throws in a row drill both have an influence on shooting skills, judging from the theoretical foundation that says both training together improve shooting skills. It was concluded that (1) there was the effect of training made or run drill on shooting skills, (2) there was the effect of ten free throws in a row drill training on shooting skills (3) there was no difference in effect between training made or run drill and ten free throws in a row drill for shooting skills.